"(MA)LINGERING ON THE DISABLED LIST". (30th January 2015) - Krautmann, Anthony C.; Solow, John L.
<x xml:space="preserve">Abstract</x> In this article, we examine two offsetting incentives that may affect a baseball player's willingness to play with injuries. We allow for the usual disincentive effects associated with long‐term contracts, while also incorporating the importance of the incentives associated with contract renewal. Our results are consistent with the previous work that showed those likely to retire at the end of their current contracts have an increased incentive to shirk. For those who expect to re‐sign a subsequent contract, however, we find that players tend to step up their effort as they approach the final year of their contract.(JEL L83)